Is behaviourism really dead? a scoping review to document the presence of behaviourism in current medical education - Ambreen Ansar; Aisha Rafi; Robina Mushtaq Rizvi (Journal of the Pakistan Medical Association, 2021)
Behaviourism is the underpinning learning theory of many teaching and assessment tools utilized to enhance the effectiveness of learning. Feedback, reinforcements, motivation, learning outcomes and objectives are few among many which are implied by the medical teachers while teaching both basic and clinical sciences to the students. The claim of Behaviourism being redundant or dead is not based on realities. Behaviourist approach is and will remain the most powerful theory to be implied in educational processes for gaining successful outcomes. Keywords: Behaviourism, Implications, Medical Education, dead, learning. Continuous...